"A perfect façade?": transparency, honor and judicial scarce resources. Issue 1 (2nd January 2019) - Shnoor, Boaz; Katvan, Eyal
ABSTRACT: While many judicial systems in the Western World are coping with a shortage of judges, the public is not always aware of the overload and its reasons. Our claim is that the reason for this is the fact that the judicial system preferred to preserve an ideal image of the judiciary and control all information about it, rather than to publicize the judicial overload problem. In this paper, we aim to show that, until recently, the issue of judicial overload was hidden from the public eye. We deal with the importance and advantages of presenting the relevant facts to the public. We shall empirically show that the judicial system has begun to legitimize the exposure of judicial overload to the public.